PERANAN KASEIN DALAM PENCEGAHAN KARIES GIGI: ROLES OF CASEIN IN DENTAL CARIES PREVENTION - Darmayanti Siregar (TALENTA, 2011)
Dental caries is the highest prevalence disease in many countries, it is shown by many studies have been performed to solve dental caries problem. Dental caries process had develop since the teeth are going to erupt in the mouth. However, it has been proved that not all food cause dental caries. Milk product which has high milk protein such casein and calcium, could prevent demineralization. By its ion calcium penetration in soluble enamel, the remineralization process will happen. It make a biofilm coated with calcium phosphoprotein and amorph calcium phosphate formation that formed along milk digestion. So it has a possibility to become an alternative food to prevent dental caries, as anticariogenic and cariostatic agent. As examples, human breast milk, bovine milk, cheese, and yogurt that would be explained in this paper. In conclusion, milk product consumption without any sugar can inhibit caries development.